2008
DOI: 10.7242/1999-6691/2008.1.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Wave propagation in rotating elastic solid

Abstract: Институт гидродинамики им. М А. Лаврентьева СО РАН, Новосибирск, 630090, Россия Рассматривается задача о распространении зон пластического состояния в безграничной среде от границы выпуклой поверхности, на которой действуют нормальное давление, касательные усилия и заданные скорости перемещений. В случае полной пластичности система квазистатических уравнений идеальной пластичности Треска, описывающих напряженно-деформированное состояние среды, является гиперболической. Для численного решения этой системы предл… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Since the wave is transverse, and the oscillatory process takes place in an isotropic medium, the displacement vector ξ is perpendicular to the wave vector k. A scientific group of authors previously suggested using this effect to create a new class of solid-state RRS. The principles of its SE construction are based on the amplitude method of revealing the informative signal and imply detecting the polarization vector rotation of the emitted transverse BAW [15,16].…”
Section: Circularly Polarized Acoustic Waves (Cpaw)mentioning
confidence: 99%
See 1 more Smart Citation
“…Since the wave is transverse, and the oscillatory process takes place in an isotropic medium, the displacement vector ξ is perpendicular to the wave vector k. A scientific group of authors previously suggested using this effect to create a new class of solid-state RRS. The principles of its SE construction are based on the amplitude method of revealing the informative signal and imply detecting the polarization vector rotation of the emitted transverse BAW [15,16].…”
Section: Circularly Polarized Acoustic Waves (Cpaw)mentioning
confidence: 99%
“…In [ 15 ] an analysis was performed of both BAW and SAW propagating in an elastic medium rotating at a constant angular velocity. The authors concluded that, under such conditions, BAW of pure linear polarization cannot propagate, and the phase velocity of SAW depends on the angular velocity of medium rotation.…”
Section: Introductionmentioning
confidence: 99%
“…In [14], an analysis was performed of both BAW and SAW propagating in an elastic medium rotating at a constant angular velocity. The authors concluded that under such conditions, BAW of pure linear polarization cannot propagate, and the phase velocity of SAW depends on the angular velocity of medium rotation.…”
Section: Introductionmentioning
confidence: 99%